Citra Perempuan dalam Novel Canting Karya Arswendo Atmowiloto: Kajian Feminisme dan Implementasinya dalam Pembelajaran Sastra di SMP - Hartono, Gesit Jatie, Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum (2017)
This study aimed to describe: (1) Setting sosiohistoris Arswendo Atmowiloto, (2) the structure of the building in the novel Canting works Arswendo Atmowiloto, (3) the image of women in the novel Canting works Arswendo Atmowiloto, and (4) implementation of research results novel Canting works Arswendo Atmowiloto as literary learning in junior high. This research is descriptive qualitative. The object of this study is the image of women contained in the Canting novel. Data collection techniques used in this study is a library. Mechanical validity of the data used in this research is data triangulation technique or source. Data analysis techniques used in this study is a semiotic technique. These results indicate that: (1) Setting Sosiohistoris Arswendo Atmowiloto was an artist of high artistic souls born in Solo, November 26, 1948. (2) The structure of the novel Canting builders can be described as follows. The themes in the novel works Arawndo Atmowiloto Canting is family life. Yan groove contained in this novel is the groove forward. Figures contained in this novel is Mr. Bei, Mrs. Bei (Tugiem), Subandini Dewaputri Sestrokusuma (Ni), Dewamurti, and MijinWening Himawan. Setting the time happens in the novel is both before and after the independence period circa 1602-1965. Place setting in the novel in general are in Surakarta with several places of Residence, namely Ngapean Sestrokusuman, Garden Ronggowarsito, Pasar Klewer, Semarang and Surabaya. The social background in the novel take place in social life in the environment of the Keraton Surakarta. (3) The image of women in the novel work of Canting Java Arswendo Atmowiloto consists of the image of women in the domestic sector (as a wife, mother, and daughters behave well) and public (religious, economic, political, education). (4) Implementation of the novel Canti g the work Arswendo Atmowiloto in learning literature in SMP especially class VIII i.e. using SK 13. Understanding the intrinsic elements of the novel (original or translation) read, and KD 13.2 Explain the theme and setting of the novel (original or translation).